Mechanical characterization of austenitic stainless steel under high-level ion-irradiation using nanoindentation experiment and simulation - Van-Thanh Pham; Jong-Sung Kim; Hyun Joon Eom; Changheui Jang (Journal of Materials Research and Technology)
The study examines the effects of high-level irradiation on the mechanical property changes and microstructural evolution of 316 stainless steel (SS) through a combination of nanoindentation tests and simulations. The irradiation conditions involve a targeted dose of approximately 200 displacements per atom (dpa) at 500 °C and transmission electron microscopy is employed to quantify void parameters (diameter, number density, and swelling) in irradiated specimen. Simulation models, based on strain-gradient crystal plasticity theory, are developed for unirradiated and irradiated states (151 dpa, 161 dpa, 200 dpa, 237 dpa, and 251 dpa), and successfully validated against nanoindentation test results. The simulation results indicate that the true bulk hardness of 316 SS exhibits a significant increase in high-level irradiation doses and is highly sensitive to void swelling. The irradiation enhances the yield stress of 316 SS while reducing its strain-hardening capacity. Additionally, higher irradiation doses or greater void swelling result in increased yield stress and reduced strain-hardening capabilities. The evolution of irradiation defect density beneath the indenter tip is attributed to the increasing annihilation of defects near the indenter tip.